POSTCOLONIAL IDENTITIES AND HYBRIDITY IN MID-CENTURY WRITING: CHINUA ACHEBE’S THINGS FALL APART, V.S. NAIPAUL’S A HOUSE FOR MR BISWAS AND JEAN RHYS’S WIDE SARGASSO SEA - Faheem Ul Haq (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This research paper examines the concepts of postcolonial identities and hybridity in three seminal mid-20th-century novels: Chinua Achebe’s Things Fall Apart (1958), V.S. Naipaul’s A House for Mr Biswas (1961), and Jean Rhys’s Wide Sargasso Sea (1966). Drawing on Homi K. Bhabha’s theoretical framework of hybridity as a “Third Space” of cultural negotiation and ambivalence, the analysis explores how these works depict the fragmentation, resistance, and reconfiguration of identities in colonial and postcolonial contexts. Achebe illustrates cultural hybridity through the clash of Igbo traditions and British colonialism in Nigeria; Naipaul portrays diasporic Indian identities in Trinidad as sites of syncretism and liminality; and Rhys highlights the tragic isolation of Creole hybridity in the Caribbean. Through comparative analysis, the paper argues that hybridity, while potentially subversive, often manifests as a source of crisis and exclusion, challenging essentialist notions of cultural purity and underscoring the enduring legacies of empire.